MAC Protocols Used by Wireless Sensor Networks and a General Method of Performance Evaluation - Joseph Kabara; Maria Calle (International Journal of Distributed Sensor Networks, 2012)
Many researchers employ IEEE802.15.4 as communication technology for wireless sensor networks (WSNs). However, medium access control (MAC) layer requirements for communications in wireless sensor networks (WSNs) vary because the network is usually optimized for specific applications. Thus, one particular standard will hardly be suitable for every possible application. Two general categories of MAC techniques exist: contention based and schedule based. This paper explains these two main approaches and includes examples of each one. The paper concludes with a unique performance analysis and comparison of benefits and limitations of each protocol with respect to WSNs.